Association of Animal Protein Adequacy with Nutritional Status: A Study on High School Adolescents in Semarang City - Melati, Sekar; Ayuningtyas, Rr. Annisa; Jauharany, Firdananda Fikri; Ulvie, Yuliana Noor Setiawati (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aimed to determine the relationship between animal protein and calcium adequacy with nutritional status. This is a cross–sectional study with 78 subjects selected by purposive sampling method. This study was conducted in State Senior High School 2 and State Senior High School 9 Semarang. The data were analyzed using Spearman's rank test. The results showed an association between animal protein adequacy and nutritional status (p=0.027, r=-0.250). There was no association between calcium adequacy and nutritional status (p=0.574, r=0.065). In conclusion, protein adequacy is associated with nutritional status among adolescents, but calcium is not.